Effect of Immunotherapy on Late Elderly Patients With Unresectable Hepatocellular Carcinoma: A Real‐World Clinical Study - Shun Kaneko; Yasuhiro Asahina; Miyako Murakawa; Shunsuke Ueyama; Hideki Watanabe; Chiaki Maeyashiki; Akiko Kusano‐Kitazume; Ayako Sato; Kozue Uchidate; Taro Watabe; Takehito Asakawa; Sho Watanabe; et al. (Cancer Medicine)
ABSTRACT Background/Aim The global aging population includes an increasing number of elderly patients with hepatocellular carcinoma (HCC). This study aimed to clarify the real‐world outcomes, prognostic factors, and appropriate administration indicators for immunotherapy in elderly HCC patients. Methods This retrospective multicenter study analyzed 286 patients with unresectable HCC who received first‐line immunotherapy (atezolizumab–bevacizumab or durvalumab‐tremelimumab) between November 2020 and January 2024. Patients were categorized into the late elderly (LE; ≥ 75 years, n = 117) and non‐late elderly (non‐LE; ≤ 74 years, n = 169) groups. Baseline characteristics, overall survival (OS), progression‐free survival (PFS), and prognostic factors were evaluated. Results The LE group had significantly poorer performance status, lower albumin–bilirubin (ALBI) scores, lower alpha‐fetoprotein (AFP) and alanine transaminase levels, higher creatinine levels, and were significantly less likely to receive post‐immune checkpoint inhibitor (ICI) treatment compared with the non‐LE group (56.2% vs. 38.4%, p = 0.0038). Median OS and PFS for the LE group were 25.6 and 10.5 months, respectively. The LE group demonstrated a comparable disease control rate (82.0%) and safety profile. The ALBI score was a significant prognostic factor for both groups. Post‐ICI treatment significantly improved OS only in the non‐LE group, even after propensity score matching for ALBI score and AFP levels. Conclusions Immunotherapy is effective and well‐tolerated in LE patients with unresectable HCC, particularly in those with preserved liver function (mALBI grade 1/2a). Post‐ICI treatment significantly benefits non‐LE patients, with limited impact on LE patients, highlighting the need for therapeutic strategies based on age and liver function.